2022
DOI: 10.1016/j.jad.2021.08.153
|View full text |Cite
|
Sign up to set email alerts
|

Mental health over nine months during the SARS-CoV2 pandemic: Representative cross-sectional survey in twelve waves between April and December 2020 in Austria

Abstract: Background There is accumulating evidence about detrimental impacts of the pandemic on population mental health, but knowledge on risk of groups specifically affected by the pandemic and variations across time is still limited. Methods We surveyed approximately n =1,000 Austrian residents in 12 waves between April and December 2020 ( n =12,029). Outcomes were suicidality (Beck Suicidal Ideation Scale), depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 36 publications
0
31
1
7
Order By: Relevance
“…Studies in the early 21st century believed that the main contents of mental health education should include publicizing the concept of psychological and physical health, realizing mental health through acceptance and respect for self, social communication, learning psychological adjustment, and introducing psychological counseling ( Marques and Braidwood, 2021 ). Some studies pointed out that the content of mental health education of college students should include the outlook on life and values, the formation of self-awareness, personality cultivation, learning habits and abilities, interpersonal communication, love and sexual psychology, emotional experience and control, the requirements of facing setbacks, job hunting, and so on, which basically covers all aspects of the college life of the students, as well as psychological test and evaluation, psychological counseling, and psychotherapy ( Niederkrotenthaler et al, 2021 ). The latest research by Kim and Hong (2021) shows that the basic contents of mental health education for Chinese college students include health concepts, self-awareness, interpersonal communication, learning, personality, emotion, frustration, sexual psychology, love, network, job selection, psychological counseling, and psychotherapy.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Studies in the early 21st century believed that the main contents of mental health education should include publicizing the concept of psychological and physical health, realizing mental health through acceptance and respect for self, social communication, learning psychological adjustment, and introducing psychological counseling ( Marques and Braidwood, 2021 ). Some studies pointed out that the content of mental health education of college students should include the outlook on life and values, the formation of self-awareness, personality cultivation, learning habits and abilities, interpersonal communication, love and sexual psychology, emotional experience and control, the requirements of facing setbacks, job hunting, and so on, which basically covers all aspects of the college life of the students, as well as psychological test and evaluation, psychological counseling, and psychotherapy ( Niederkrotenthaler et al, 2021 ). The latest research by Kim and Hong (2021) shows that the basic contents of mental health education for Chinese college students include health concepts, self-awareness, interpersonal communication, learning, personality, emotion, frustration, sexual psychology, love, network, job selection, psychological counseling, and psychotherapy.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Existing literature has highlighted the rates of healthcare worker nonfatal suicidal behavior at different time points in the pandemic. A longitudinal Austrian study that was conducted between April and December 2020 by Niederkrotenthaler et al (2022) showed that healthcare workers were at higher risk of experiencing suicidal ideation than nonhealthcare workers, even after controlling for occupational risk of exposure to COVID-19. However, a cross-sectional study conducted by Mamun et al, (2020) in Bangladesh (April 2020) did not show any increased risk of nonfatal suicidal behavior in healthcare workers compared to the general population.…”
Section: Impact Of the Covid-19 Pandemicmentioning
confidence: 99%
“…O risco aumentado das ocorrências de violência doméstica durante a pandemia da Covid-19 deu-se pelo aumento da proximidade física entre as pessoas durante a quarentena. Outros fatores de risco são: morar em grandes famílias; com outras pessoas com Covid-19 ou trabalhar em casa (NIEDERKROTENTHALER et al, 2021). Ou seja, a falta de espaço pessoal aumenta o nível de pressões interpessoais, o que pode levar ao conflito (UZOBO et al, 2021).…”
Section: Fundamentação Teóricaunclassified
“…É importante ressaltar que a violência doméstica é fator de risco para ideação e comportamento suicida, o que indica comprometimento da saúde mental (NIEDERKROTENTHALER et al, 2021). Se esta situação permanecer, muitas mulheres morrerão em suas casas (UZOBO et al, 2021).…”
Section: Fundamentação Teóricaunclassified
See 1 more Smart Citation